Potensi Pengaruh Radiasi Gelombang Elektromagnetik Telepon Seluler Terhadap Kesehatan - Yushardi Yushardi; Sudarti Sudarti; Muhammad Najih Hamdi (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Mobile phones are currently undergoing development, with a variety of conveniences that they can do. Cell phones, or what is known as smartphones or smartphones at this time, produce electromagnetic wave radiation that affects the health of the human body. Aims: Knowing the effect of mobile phone electromagnetic radiation on human brain health. Method: Research using narrative-type Literature Review, journals, and books nationally and internationally. Electromagnetic radiation from mobile phone use affects several human health disorders. Results: Indications of these health problems can be in the form of tumors and cancer in the brain, which can cause stress, and disruption of sperm, gliomas, and red blood cells. Interference caused by the electromagnetic radiation of mobile phones to health is still a polemic. Conclusion: Electromagnetic radiation from mobile phone use can potentially cause some health disorders.